Introduction to Theano - Ketkar, Nikhil (Deep Learning with Python, 2017)
In this chapter we introduce the reader to Theano, which is a Python library for defining mathematical functions (operating over vectors and matrices), and computing the gradients of these functions. Theano is the foundational layer on which many deep learning packages like Keras are based.